Digital Energy Hub for Optimizing Energy Usage: A Review - Bin Kasim, Hairoladenan; Bin Ibrahim, Zul-Azri; Bin Mohamed Ariff, Mutahir (International Journal of Engineering and Technology, 2018)
Energy usage as it relates to its security and management is an important aspect that all organizations having a vested stake in power production should be concerned with in these coming years. In this respect, harnessing the knowledge so that it may benefit various sectors, from the power producer right down to the customers, can be achieved by way of the digital energy hub, as proposed in this paper. We first put into context the workings and functions of such a digital platform, and then proceed to outline how it could benefit the many parties involved. Lastly, we take into account the challenges that needs to be addressed for its successful implementation, in which information security and privacy is a top priority amongst other issues.Â Â